Ավետիս Ահարոնյանը և Հայկական հարցը - Հովհաննես Զատիկյան (ՀՀ ԳԱԱ հրատ.)
Ав. Агаронян еще в 1890-х годах в своих многочисленных статьях показал позицию великих держав по отношению к Армянскому вопросу. Поэтому в начале своей деятельности в Европе он пытался создать общественно-политическое мнение для разрешения Армянского вопроса, однако, став очевидцем трагических событий, пережил идейный поворот, придя к выводу, что в решении Армянского вопроса заинтересован только сам армянский народ. Av. Аharonyan showed the position of the Great Powers in relation to the Armenian question in numerous articles still in the 1890s. Therefore, at the beginning of his political activity in Europe he tried to create a political and social opinion for the solution of the Armenian question, however, becoming the eyewitness of the tragical events, going through an ideological turn, he came to the conclusion that only the Armenian people were interested in the solution of the Armenian question.
Keywords: History; D History